Multimodal literacy: Unfolding reading path in children’s picture book and its potential for EFL classrooms - Damayanti, Ika Lestari; Febrianti, Yusnita (Indonesian Journal of Applied Linguistics, 2020)
This paper reports on an investigation into the reading path patterns in a children’s picture book. The primary investigation focused on the semiotic resources involved in the construction of meanings in picture books, i.e. language and image elements. These semiotic resources provide insights into the unfolding of the storylines in the observed picture book. In order to detail the roles of these resources, a picture book entitled Tacky the Penguin (Lester, 1988) was selected and examined by employing two methods: Kress and Van Leeuwen’s (1996, 2006) structure of information value and Royce’s (1998) Intersemiotic Complementarity. The results of the analysis suggest that the whole picture book is built from a page-by-page reading path that allows for a linear and non-linear reading path. While each page presents a different layout of information value, the general pattern leads to a linear reading path from the beginning up to the end of the picture book. The mapping of the reading path is reinforced by the interrelated meanings between verbal and visual resources on the page. Drawing on the analysis results, this paper offers the delve into the flow of information from the language and image resources in the picture books that can be used to inform practical use of picture books in EFL classrooms.